IMPLANTAÇÃO DE PROTOCOLO DE ACOLHIMENTO E CLASSIFICAÇÃO DE RISCO EM UMA MATERNIDADE DE RISCO HABITUAL - Mayer, Maria Aparecida Brizola (2017)
The purpose of this study was to establish a Protocol of Reception and Risk Classification in the care of pregnant women in a maternity at usual risk. Therefore, the following specific objectives were listed: To adapt the Protocol of Reception and Risk Classification of the Ministry of Health in the care of pregnant women in a maternity of habitual risk; and, To discuss with the professionals working in a maternity unit of habitual risk the adequacy of the Protocol of Reception and Classification of Risk to the pregnant women. To meet the first specific objective, an action research was conducted through the focal group technique, with the participation of obstetrician physicians, obstetrical nurses, residents of the second year of residence in obstetric nursing and obstetric area teachers, working in a maternity of habitual risk of the interior of the state of Rio Grande do Sul, from May to October 2016. For the second objective, a qualitative research was carried out in April 2017, with the same population, about the discussion of the appropriate protocol in order to verify the fragilities and potentialities of the same. From the resulting data and analyzed by the strategic focal analysis, the importance of the protocol for maternity emerged, weak and strong points for its implantation regarding the internal and external aspects and socialization of the adaptations of the flowcharts. Regarding the second article, two lines of discussion emerged that were based on: Potentials or internal and external forces for the implantation of the Protocol of Reception and Risk Classification for pregnant women; and, Fragilities, internal and external weaknesses for implantation of the Protocol of Reception and Classification of Risk to pregnant women. Based on the data, the product generated, through the research process, was the Implementation of a Protocol of Reception with Risk Classification adequate for a maternity of risk habitual in the interior of the state of Rio Grande do Sul. It was concluded that the results of this research allow to identify that there are gaps in the effective implementation of the protocol, however, there is a need to work with the local manager regarding the restructuring of the physical aspects of maternity hospital, as well as to size human resources so that The Reception and Risk Classification protocol can be used in order to subsidize comprehensive care for the pregnant women attended in this maternity hospital, since it is well known that the protocol implementation optimizes the integrality of care.